2004
DOI: 10.1074/jbc.m310505200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topology and Nicastrin-enhanced Endoproteolysis of APH-1, a Component of the γ-Secretase Complex

Abstract: APH-1, presenilin, nicastrin, and Pen-2 are proteins with varying membrane topologies that compose the ␥-secretase complex, which is responsible for the intramembrane proteolysis of several substrates including the amyloid precursor protein. APH-1 is known to be necessary for ␥-secretase activity, but its precise function in the complex is not fully understood, and its membrane topology has not been described, although it is predicted to traverse the membrane seven times. To investigate this, we used selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 45 publications
3
55
0
2
Order By: Relevance
“…The structure of Osenkowski et al (18) revealed a somewhat porous structure that was interpreted to have several domains on the extracellular side and solvent-accessible low density cavities in the transmembrane region of the complex. In contrast and despite having comparable dimensions, our structure appears to be more compact, with the extracellular region consisting of a single domain that is consistent with the dimensions of the ectodomain of NCT (65)(66)(67). In addition, instead of several low density cavities within the postulated transmembrane region (18), we observed a single central chamber that interfaces with a concave surface on the extracellular region.…”
Section: Discussionsupporting
confidence: 52%
“…The structure of Osenkowski et al (18) revealed a somewhat porous structure that was interpreted to have several domains on the extracellular side and solvent-accessible low density cavities in the transmembrane region of the complex. In contrast and despite having comparable dimensions, our structure appears to be more compact, with the extracellular region consisting of a single domain that is consistent with the dimensions of the ectodomain of NCT (65)(66)(67). In addition, instead of several low density cavities within the postulated transmembrane region (18), we observed a single central chamber that interfaces with a concave surface on the extracellular region.…”
Section: Discussionsupporting
confidence: 52%
“…For instance, the APH1 TMD(s) interacting with NCT has not been determined but may reside in the second half of APH1 (Fortna et al, 2004) (Fig. 3).…”
Section: Journal Of Cell Science 416mentioning
confidence: 99%
“…One essential member of ␥-secretase complex is APH-1, a sevenpass membrane protein (Francis et al, 2002;Fortna et al, 2004) that forms a stable subcomplex with nicastrin (Gu et al, 2003;Hu and Fortini, 2003;LaVoie et al, 2003;Takasugi et al, 2003). Unlike Caenorhabditis elegans and Drosophila in which a single Aph-1 gene exits, three Aph-1 genes are found in mice; Aph-1a is localized to chromosome 3, whereas Aph-1b and Aph-1c are arranged in tandem (ϳ20 kb apart) on chromosome 9.…”
Section: Introductionmentioning
confidence: 99%